Handbook of Therapeutic Antibodies - Dübel, Stefan; Reichert, Janice M. (Wiley Blackwell, 2014)
Still the most comprehensive reference source on the development, production and therapeutic application of antibodies, this second edition is thoroughly updated and now has 30% more content. Volume 1 covers selection and engineering strategies for new antibodies, while the second volume presents novel therapeutic concepts and antibodies in clinical study, as well as their potential. Volumes 3 and 4 feature detailed and specific information about each antibody approved for therapeutic purposes, including clinical data. This unique handbook concludes with a compendium of marketed monoclonal an.